2021
DOI: 10.3390/brainsci11020133
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Circulating Microparticle Subpopulations in Incidental Cerebral White Matter Hyperintensities: A Multimodal Study

Abstract: Asymptomatic (or “silent”) manifestations of cerebral small vessel disease (CSVD) are widely recognized through incidental findings of white matter hyperintensities (WMHs) as a result of magnetic resonance imaging (MRI). This study aims to examine the potential associations of surrogate markers for the evaluation of white matter integrity in CSVD among asymptomatic individuals through a battery of profiling involving QRISK2 cardiocerebrovascular risk prediction, neuroimaging, neurocognitive evaluation, and mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…The data for this study were derived from a well-characterized cohort established from a recent study on CSVD based at a single centre, Hospital Universiti Sains Malaysia (HUSM), Kubang Kerian, Kelantan 32 . Approximately 96% of this region is predominated by Malay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data for this study were derived from a well-characterized cohort established from a recent study on CSVD based at a single centre, Hospital Universiti Sains Malaysia (HUSM), Kubang Kerian, Kelantan 32 . Approximately 96% of this region is predominated by Malay.…”
Section: Methodsmentioning
confidence: 99%
“…MRI acquisition was performed at 3.0 Tesla using a 32-channel head coil MRI scanner (Philips Achieva) with the b -value of 1000 s/mm 2 . The MRI acquisition parameters are as the followings; 3D-T1: echo time (TE) = 10 ms, repetition time (TR) = 678 ms, reconstruction matrix = 512 × 512 × 40, field of view (FOV) = 230 mm, voxel size = 0.45 mm × 0.45 mm, slice spacing = 0 mm, slice thickness = 2.5 mm, flip angle = 70°, and 180 contiguous sagittal slices orientation; T2: TE = 80 ms, TR = 3000 ms, reconstruction matrix = 512 × 512 × 24, FOV = 230 mm, voxel size = 0.45 × 0.45, slice spacing = 1.0 mm, slice thickness = 2.5 mm, and flip angle = 90°; 3D-fluid attenuated inversion recovery (FLAIR): TE = 125 ms, TR = 11,000 ms, TI = 2800 ms, reconstruction matrix = 512 × 512 × 24, FOV = 230 mm, voxel size = 0.45 mm × 0.45 mm, slice spacing = 0 mm, slice thickness = 2.5 mm, flip angle = 90°, and 170 contiguous sagittal slices orientation 32 . The image of the circle of Willis and its tributaries were captured using 3D-TOF MRA with the following parameters: TE = 3.5 ms, TR = 20 ms, reconstruction matrix = 720 × 720 × 200, FOV 200 mm, voxel size = 0.28 mm × 0.28 mm, slice spacing = 1.0 mm, slice thickness = 0.6 mm, flip angle = 20°.…”
Section: Magnetic Resonance Imaging (Mri) Acquisition Protocolmentioning
confidence: 99%
“…(1) the occlusion of small cerebral penetrating arteries and (2) arteriosclerosis or lipohyalinosis (i.e., thickening and/or damage of the arteriolar wall) [42]. Nevertheless, it is now accepted that the majority of macrostructural changes observed from neuroimaging manifestations of CSVD are plausibly due to underlying meso-structural responses, such as obstruction of cerebral microcirculation flow [43]. In this case, the arteriolar narrowing and/or occlusion may result in a symptomatic ischemic event, as seen in small lacunar infarcts in the traditional CSVD spectrum, or simply occult.…”
Section: Pathomechanism Of Csvd and Roles Of Oxidative Stress-neuroin...mentioning
confidence: 99%
“…Besides modulating hypertension, a previous in vitro study showed the inhibitory effect of natural honey on platelet aggregation and blood coagulation [151]. Whereby, increased platelet aggregation and hypercoagulation have been proposed as an emerging molecular mechanism of CSVD [43,114]. Interestingly, in a recent in vivo study, honey has been found to exhibit an antiplatelet effect by increasing bleeding time when a group of mice was given commercial honey for 12 days as compared to that aspirin [164].…”
Section: Pre-clinical Evidence On Anti-hypertensive Effects Of Honeymentioning
confidence: 99%
“…Greater multimodal and advanced magnetic resonance imaging (MRI) technologies including brain volume, diffusion tensor imaging (DTI), functional magnetic resonance imaging (fMRI) have been applied in the evaluation of cognitive function of CSVD patients ( 7 ). Screening test for cognitive impairment in elderly CSVD patients by means of imaging techniques is a promising approach.…”
Section: Introductionmentioning
confidence: 99%